1993
DOI: 10.1002/jbm.820270105
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calcium phosphate ceramic composition and structure on in vitro behavior. I. Dissolution

Abstract: Synthetic calcium phosphate ceramic (CPC) surfaces can be transformed to a biological apatite through a sequence of reactions which include dissolution, precipitation, and ion exchange. By virtue of the reactions being material-dependent, it is important to determine parametric rate effects. In this study we focused on the effect of stoichiometry and crystal structure of CPCs on the dissolution kinetics. Monophase, biphase, and multiphase CPCs with a Ca/P ratio equal to or greater than 1.5 were studied. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
237
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(248 citation statements)
references
References 17 publications
9
237
2
Order By: Relevance
“…122 On the basis of the composition and stoichiometry of a calcium-phosphate ceramic, important physical properties such as degradation rate, modulus, and processability can be changed. [123][124][125][126] Research on TCP materials has revealed that the degradation rate is too rapid in vivo, while synthetic versions of HAp degrade too slowly to allow native tissue integration. This phenomenon motivated the development of BCP and bio-glasses which have tunable (to some degree) degradation rates based on the relative magnitude of TCP (more commonly b-TCP) and HAp in a composite ceramic.…”
Section: Bone Biomimeticsmentioning
confidence: 99%
“…122 On the basis of the composition and stoichiometry of a calcium-phosphate ceramic, important physical properties such as degradation rate, modulus, and processability can be changed. [123][124][125][126] Research on TCP materials has revealed that the degradation rate is too rapid in vivo, while synthetic versions of HAp degrade too slowly to allow native tissue integration. This phenomenon motivated the development of BCP and bio-glasses which have tunable (to some degree) degradation rates based on the relative magnitude of TCP (more commonly b-TCP) and HAp in a composite ceramic.…”
Section: Bone Biomimeticsmentioning
confidence: 99%
“…Although degradation of CaP has been assessed in different solutions [31][32][33][34][35], the simulation of the resorption process by osteoclasts requires working in solutions at acidic pH. This is because resorption by mature osteoclast proceeds through the development of a tight ring-like zone of adhesion (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The discontinuous measurement techniques include pharmacopoeia methods such as the BP (British Pharmacopoeia) and USP (United States Pharmacopeia) methods and other intermittent sampling-and-analysis methods [29,30]. The pH values ranged from ≈3 to 7.4 in these dissolution tests.…”
Section: Introductionmentioning
confidence: 99%